Mighty Thor. Vol. 4, The war Thor - Aaron, Jason (Marvel Worldwide, 2018)
"Who is the new Ultimate Thor? The Ultimate Universe's Thor died defending the Multiverse, but his hammer remains. Who wields it now? Ponder that question along with Jane Foster, the Mighty Thor, as she faces the Ultimate team-up! War is coming to the Ten Realms - and when the Queen of Cinders sets them ablaze, even the combined might of not one, not two, but three Thors may not be enough to put out the flames! Meanwhile, Malekith's army grows and the looming conflict reaches Asgard's doorstep! But even the fire of Muspelheim pales beside the fury of the Ultimate Thor...and with his thunder comes his vengeance!" --